Merayakan Toleransi: Studi atas Masyarakat Muslim Pandeglang - Ahmad Abrori (Refleksi: Jurnal Kajian Agama dan Filsafat, 2006)
The issue of tolerance is actually related to the articulation of discourse and the realization of practices in real life. Both are interrelated and support each other for the creation of good relations among religious communities. Unfortunately, what becomes the daily reality is not supported by a good discourse articulation. As a result, there is tension in discourse among the people of Pandeglang when discussing tolerance. This study focuses on the views of the Pandeglang community regarding tolerance among religious communities. The initial interest in conducting this study is due to the fact that in Pandeglang, there is not a single non-Muslim place of worship built there. Looking at the composition of its population, there are several non-Muslim communities living amidst the predominantly Muslim community.